The Present of Action and its Futuristic in the Verses of the Story of the People of the Cave (The International Journal of Educational Sciences and Arts, 2024)
The Qur'anic stories constitute one of the most important purposes for explanation, lesson, and measuring current events against past events that the Qur'an wants to convey to us. The Qur'anic story has been formulated in various ways, according to what the context requires, some of which are detailed, and some of which are summarized. The story of the People of the Cave is one of the stories that have been detailed. This research deals with the story of the People of the Cave in terms of using the verb to know the style of the Qur'anic story from the gate of grammar.This was discussed through two important meanings: the timeliness of the verb used, and the futurestic of the verb in the story of the People of the Cave. This section sheds light on how the story, despite the pastness of its time, was formulated in a style that indicates the present and the future so that the story is alive and renewed. The style of dialogue in this story was also discussed, which made the text lively and vibrant with vitality and movement.It was concluded that researching the Qur'anic text through grammar leads to knowledge that adds a dimension to the Qur'anic interpretation that can be used to know the secrets of the Holy Qur'an.
Keywords: The People of the Cave; The Qur'an; The Story; The Verb; Dialogue